Skin reactions to thimerosal and Leishmania in dogs from a leishmaniasis endemic area: it is better to keep them apart - Moacir Paranhos-Silva; Lain C Pontes-de-Carvalho; Geraldo G de Sá Oliveira; Eliane Góes Nascimento; Washington LC dos-Santos (Memorias do Instituto Oswaldo Cruz, 2001)
Positive Montenegro's skin test is a delayed type hypersensitivity reaction widely used as indicative of previous infection with Leishmania in both humans and dogs. Montenegro's antigen consists of a crude Leishmania antigen solution, usually containing thimerosal as preserving agent. In this work it is shown that a large proportion of dogs (11 out of 56) examined in an endemic area of leishmaniasis presented induration at the site of injection of a diluent containing thimerosal alone. This clearly demonstrates that thimerosal leads to a high number of false positive skin reactions in dogs and that its use in Montenegro's skin test antigenic preparations should be avoided.